Team-Based Project Implementation in Public Relations Learning Through PR Campaign Video Analysis - Anis Susanti; Nina Oktarina (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2023)
This study aims to analyze the implementation of the Team-Based Project Learning method in Public Relations learning for Office Administration students of the Economics Faculty at Universitas Negeri Semarang. Some difficulties faced by office administration students in developing their skills become more complicated after the pandemic due to online learning. Online learning focuses more on lecturers than students, so it has not been able to solve the difficulties in developing their public relations skills. Team-Based Project Learning is implemented because it demands the ability of the students themselves to solve problems in working as public relations, while teachers as facilitators of ideas for problems that must be solved through PR-Campaign Video. This research uses a qualitative descriptive approach. Data analysis uses Milles and Huberman with data collection, data reduction, and conclusion. The data sources used are observations, interviews, and documentation. The results of this study showed that students who usually learn passively, produce active abilities in their groups because each of the students has a role in the groups to analyze the PR-Campaign video. Each group in team-based project learning has various ways of analyzing the project and has different creativity to present the results.